Dakwah Digital dan Tantangan Verifikasi Hadis: Studi Terhadap Pemahaman Audiens di Media Sosial - Zulfirman Manik; Nur Jannah; Moh Ikhsan Azmi; Fatonah Rahmah; Riza Fitri Lubis (Albayan Journal of Islam and Muslim Societies, 2025)
The advancement of information technology has transformed the methods of Islamic preaching (da'wah), positioning social media as a primary platform for disseminating religious messages. Amid the rapid and massive flow of information, the spread of hadiths through digital media faces serious challenges in terms of verification and source authenticity. This study aims to understand how social media audiences perceive the importance of hadith verification in the context of digital da'wah and how such understanding influences their reception of religious content. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews, participatory observation, and content analysis of social media platforms. The analysis is grounded in information reception theory and digital religious literacy. The findings reveal a diversity of audience understanding regarding hadith authenticity, influenced by educational background, trust in digital preachers, and exposure to religious content. The analysis shows that low levels of digital Islamic literacy contribute to the widespread dissemination of inauthentic hadiths. Compared to previous studies and relevant theories, this research emphasizes the need for a systematic enhancement of digital religious literacy. In conclusion, audience understanding of hadith verification remains uneven, highlighting the need for da'wah strategies that are not only informative but also educational within the social media landscape.